Rapid glycolytic activation accompanying innate immune responses: mechanisms and function - Namgaladze, Dmitry; Brüne, Bernhard (Frontiers in Immunology, 2023)
Innate immune responses to pathogens, mediated by activation of pattern recognition receptors and downstream signal transduction cascades, trigger rapid transcriptional and epigenetic changes to support increased expression of pro-inflammatory cytokines and other effector molecules. Innate immune cells also rapidly rewire their metabolism. The most prominent metabolic alteration following innate immune activation is rapid up-regulation of glycolysis. In this mini-review, we summarize recent advances regarding the mechanisms of rapid glycolytic activation in innate immune cells, highlighting the relevant signaling components. We also discuss the impact of glycolytic activation on inflammatory responses, including the recently elucidated links of metabolism and epigenetics. Finally, we highlight unresolved mechanistic details of glycolytic activation and possible avenues of future research in this area.